Confined and unconfined nucleate boiling of HFE7100 in the presence of nanostructured surfaces - Souza, R. R.; Cardoso, E. M. [UNESP]; Passos, J. C. (Elsevier, 2018)
This article presents experimental results for the confined and unconfined nucleate boiling of saturated HFE7100 (C4F9OCH3) at atmospheric pressure and using nanostructured copper discs as heating surfaces. The nanostructures studied consisted of nanoparticles of maghemite (Fe2O3) on the heating surface, comprised of a copper disc. Different values for the diameter (10 and 80 nm) and roughness (Ra = 0.02 µm and 0.16 µm) were studied. The nanoparticle adhesion on the heating surface plays a more important role in the confined boiling process than the surface roughness. As an original result, it was demonstrated that for a confinement with a gap length of 0.1 mm and heat flux of 40 kW/m2 the heat transfer coefficient (HTC) increased by 31% and 100% for the cases with the deposition of nanoparticles of 10 nm and 80 nm, respectively. However, without the nanoparticles the HTC decreased by 21% when compared with the reference case, that is, a smooth plate (Ra = 0.02 µm) and unconfined boiling.
Keywords: Confined nucleate boiling; Heat transfer coefficient; Nanoparticle size; Surface roughness